World Salt Awareness Week: A call to action for reducing salt intake in Malaysia - Yook Chin Chia; Siew Mooi Ching; Nik Sherina Hanafi (Malaysian Family Physician)
Cardiovascular diseases remain a primary contributor to death worldwide, with hypertension being a key determinant. Excessive salt intake is a contributing factor of high blood pressure and cardiovascular diseases. To address this, the World Health Organization recommends keeping daily salt consumption under 5 g and aiming for a 30% decrease by 2025. In Malaysia, efforts to reach this target have faced delays. A local study found that 79% of Malaysians consume an average of 7.9 g of salt per day, which is significantly higher than the WHO’s recommendations. Despite efforts such as voluntary food reformulation, mandatory sodium labelling and public education campaigns, challenges remain. Industry reluctance, low consumer awareness and inadequate enforcement slow down such efforts. This commentary reviews these issues and suggests applicable approaches to strengthen Malaysia’s salt reduction strategies.